Draft Annual Plan 1989-90 Volume : I An Overview Government of Assam - Planning Commission (Planning Commission, 1989)
Situated in the extreme north-east of the country Assam forms the core of the North Eastern Region comprising Arunachal Pradesh, Manipur, Meghalaya, Mizoram Nagaland and Tripura. It has common borders with all other six States of the region along with West Bengal besides, international borders with Bangladesh and Bhutan. The whole of North Eastern Region is linked with the rest of India by a slender 'corridor through North Bengal.
Government of Assam, Planning and Development Department